Inovasi Formulasi Food Pairing Serbat Sparkling Minuman Tradisional Pendamping Sandwich Generasi Z Sebagai Moodbooster Fungsional - Hamzah Akram Maulana; Davin Goneril; Auliadini Febrianti; Vonny Fabiola; Fhebyta Solafidae M; Angelica Virginia; Yohana. S. Kusuma Dewi (Jurnal Agritechno, 2025)
Sparkling serbat is an innovative traditional beverage derived from the serbat water of the Pontianak Malay tribe, enhanced with carbonation (soda) to increase its appeal as a cultural revitalization effort. This study utilized a Randomized Complete Block Design (RCBD) with one factor, namely the serbat-to-soda ratio (F), comprising 4 treatment levels (f0 = serbat:soda = 0:1, w/w; f1 = serbat:soda = 1:1, w/w; f2 = serbat:soda = 1:2, w/w; f3 = serbat:soda = 1:3, w/w; f4 = serbat:soda = 1:4, w/w), with five replications. The study aimed to identify the best ratio of soda to sparkling serbat suitable as an accompaniment to sandwiches, the favorite food of Generation Z. The research incorporated various spices, along with sodium bicarbonate and citric acid at varying concentrations, tested against several parameters (antioxidant activity, total flavonoid content, total acidity, total dissolved solids, pH, and color). The results showed that formulation F1, with sodium bicarbonate at 0.102 grams and citric acid at 0.123 grams, exhibited the highest antioxidant activity and total acidity, measuring 32.96% and 8.96%, respectively. The highest total flavonoid content was observed in formulation F4, with a value of 173.74%. The addition of sodium bicarbonate and the reduction of citric acid affected the antioxidant activity and total flavonoid content in the sparkling serbat. Consumer acceptance indicated that sample F3 was the best treatment in terms of antioxidant content and consumer preference.Keywords: Serbat, Pontianak, Sparkling, Soda